Perlindungan Hukum terhadap Tenaga Kesehatan dalam Pelayanan Medis yang Merugikan Pasien dari Perspektif Hukum Kesehatan - Novi Afsari; Avy Permata Sari; Fatmasari Diahpermata Djajaputri Adhimutiahara; Ida Bagus Gede Adiguna Wibawa; Marsudi Dedi Putra (Yayasan Literasi Sains Indonesia, 2026)
The phenomenon of medical disputes following the enactment of Law No. 17 of 2023 indicates the vulnerability of health workers to criminalization when medical services result in patient harm. Despite the issuance of the latest regulations, there is a research gap regarding the operational boundaries between excusable medical risks and punishable professional negligence. This study aims to analyze the legal protection mechanisms for health workers from the latest health law perspective. The research method used is normative legal research with statutory and conceptual approaches. The results show that Law No. 17 of 2023 provides legal protection through professional immunity rights, provided that standard operating procedures are met, along with a filtering mechanism through the Disciplinary Body to prevent premature criminalization. The study concludes that legal protection for health workers is integrative, balancing professional career certainty and patient protection rights through restorative justice. It is recommended that the government immediately issue technical implementing regulations regarding the examination procedures of the Disciplinary Body to ensure uniform procedures for law enforcement officers. Furthermore, health service facilities need to strengthen legal aid systems and risk management to mitigate the escalation of medical disputes in the future.